The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep39177
|View full text |Cite
|
Sign up to set email alerts
|

Global map of oxytocin/vasopressin-like neuropeptide signalling in insects

Abstract: Oxytocin and vasopressin mediate a range of physiological functions that are important for osmoregulation, reproduction, social behaviour, memory and learning. The origin of this signalling system is thought to date back ~600 million years. Oxytocin/vasopressin-like peptides have been identified in several invertebrate species and they appear to be functionally related across the entire animal kingdom. There is little information available about the biology of this peptide G protein-coupled receptor signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…1B). Because there was only 1 significant hit in the L. neglectus transcriptome for each (IR and IP), we suggested that the OT/VP-like signaling system in L. neglectus is composed of a single peptide and receptor, as is observed in other insect species (3). After cloning of the L. neglectus receptor into a suitable expression vector and synthesis of the inotocin peptide, we performed second messenger analysis and binding studies of this signaling system in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1B). Because there was only 1 significant hit in the L. neglectus transcriptome for each (IR and IP), we suggested that the OT/VP-like signaling system in L. neglectus is composed of a single peptide and receptor, as is observed in other insect species (3). After cloning of the L. neglectus receptor into a suitable expression vector and synthesis of the inotocin peptide, we performed second messenger analysis and binding studies of this signaling system in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier work, we discovered the genes and transcripts encoding the IP and IR in insects and particularly in ants (3, 22). We validated the expression of the receptor by molecular cloning and confirmed the functionality of the peptide/receptor pair by pharmacological characterization of the inotocin signaling system of the black garden ant ( L. niger ) (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most modern vertebrates have at least two oxytocin-and vasopressin-like peptides, whereas most invertebrates, including mollusks, annelids and many insects,166,167 have only one. Most modern vertebrates have at least two oxytocin-and vasopressin-like peptides, whereas most invertebrates, including mollusks, annelids and many insects,166,167 have only one.…”
mentioning
confidence: 99%